The Analysis of Tax Avoidance Determinant on The Property and Real Estate Companies - Turyatini Turyatini (Jurnal Dinamika Akuntansi)
The tax authorities had found some modus that done by developers on property tax avoidance and supported by potential loss of tax income from property and real estate sector at 2012-2015. This phenomenon show that tax avoidance still practiced by most of property and real estate companies, so that its became the target of intensive monitoring by the tax authorities. The aim of this research is to analyze the effect of leverage, company size, sales growth, institutional ownership, and independent commissioners on tax avoidance in property and real estate companies The population of this research is real estate property company which number 47 companies and the sample is 18 companies is done by using purposive sampling method. The instrument used to analyze the hypothesis is multiple linear regression. The results show that leverage and company size have significant effect on tax avoidance. Sales growth, institutional ownership and independent commissioners do not have significant effect on tax avoidance.